The Silicon Valley We Don’t Want to Have: A review of Antonio García Martínez, Chaos Monkeys: Inside the Silicon Valley Money Machine - Campbell, Leith H. (Journal of Telecommunications and the Digital Economy, 2017)
This article is a review of Antonio García Martínez’s book, Chaos Monkeys: Inside the Silicon Valley Money Machine, published in 2016, which tells the story of the author’s time in Silicon Valley. An area of major interest is his time at Facebook, where he helped develop an online advertising exchange. The book is a warts-and-all account that describes many undesirable aspects of “Silicon Valley culture”. While the book is overly self-indulgent, it could valuably be read by policy makers interested in start-ups and business culture.